Development of Interactive Learning Multimedia to Improve the Result of Underhand Passing and Underserving Skill in Volleyball Games of IV Grade in SD Negeri 106790 Sei Mencirim - Ari Mecky Prawira Ketaren; Agung Sunarno; Nimrot Manalu (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The objective of this research is to develop interactive learning multimedia. This research used Research and Development Method. The results in the development stage of interactive learning multimedia show: (1) the assessment of material experts was high feasible criteria with an average score of 4.68, (2) the assessment of design experts was high feasible criteria with an average score of 4.66, (3) the assessment of the media I was in the criteria of high feasible with an average score of 4.57, (4) the assessment of media experts II was in the criteria of high feasible with an average score of 4.85. Interactive learning multimedia was very effective in improving student skills in underhand passing and underhand service and can improve student learning outcomes in underhand passing and underhand service. It was proved that the average student skill result when performing underhand service after used interactive learning multimedia is 81.5 with N-Gain 0.6 medium category, the average student skill result when performing underhand service after used learning multimedia interactive was 86.75 with N-Gain 0.7 high category. The average student learning outcomes using interactive learning multimedia was 89 with an N-Gain of 0.8 "High". While the results of the lower passing t test obtain a sig value <0.05. After analyzing the data, the final test showed sig <0.05, mean Ha was accepted and Ho was rejected. Significant value of passing below 0.003 <0.05 which mean significant with a sig level of 5%, then sig value of service below 0.000 <0.05 which mean significant with a sig level of 5%. It proved that interactive learning multimedia was more effective and proven to increase student skill outcomes in carried out underhand passing and underserving as well as improved student learning outcomes in underhand passing and underserving material in IV grade of SD Negeri 106790 Sei Mencirim.